3D branched rutile TiO2 @ rutile SnO2 nanorods array heteroarchitectures/carbon cloth with an adjustable band gap to enhance lithium storage reaction kinetics for flexible lithium-ion batteries. (10th September 2020) - Liu, Qi; Wang, Linlin; Zhao, Kangning; Yan, Wei; Liu, Minmin; Wei, Denghu; Xi, Lili; Zhang, Jiujun
Abstract: In this paper, novel arrays of rutile SnO2 nanorods (r-SnO2 -NRs) are successfully grown vertically on the arrays of the rutile TiO2 nanorods (r-TiO2 -NRs) and directly supported on the carbon cloth (CC) to form a hierarchical nano-heterostructure material (r-TiO2 -NRs@r-SnO2 -NRs/CC) through a two-step hydrothermal process. Such a reverse core-shell nano-heterostructure design with r-SnO2 -NRs as shell layer epitaxially grown on the r-TiO2 -NRs backbone is directly used as a binder-free and flexible lithium-ion batteries (LIBs) anode. Both high initial Coulombic Efficiency and high reversible capacity are demonstrated, which are much better that those of the single components. The enhanced electrochemical performances are attributed to a heterostructure of r-TiO2 -NRs and r-SnO2 -NRs as well as the unique branched nanostructures. The density functional theory (DFT) analysis further manifest that such a r-TiO2 -NRs@r-SnO2 -NRs heterostructure can achieve the faster electron transport kinetics than their single components due to a change in the energy band gap after heterogenization. Due to the arrayed and crosslinked structure of such a anode material and its flexible CC supporter, the strong structure stability and flexibility can be realized for flexible LIBs.